EDUCATION OF A DEVELOPED GENERATION AS AN IMPORTANT FACTOR IN INCREASING THE EFFICIENCY OF EDUCATION - Gullola Kurbanova; Abdukakhor Zaparov; Bahrom Kurbanov; Ahmadbek Zafarov (Galaxy International Interdisciplinary Research Journal, 2021)
The article describes the idea that a harmoniously developed generation should be a creator and devotee, not a consumer of our renewed society, the main tasks of educators and the process of personal development with students.